Estudo comparativo da resistência a corrosão de uma liga metálica (aço 1020) revestida com Zn/Ni e níquel - Dantas, Jefferson Kenede Jales (Universidade Federal Rural do Semi-Árido, 2019)
Galvanoplasty is a method used to coat a metal with another forming a thin layer, this layer has the purpose of making the base metal to be coated does not have contact with the corrosive medium (electrolyte), in addition, it has decorative purpose, to have a resistance to the friction and bring the recovery of worn material. The corrosive process impairs mechanical strength, electrical conductivity and other characteristics such as thermal transmissibility, expansion and contraction coefficients, and alters the appearance of materials. Many metals are exposed to moisture, salinity and temperature variations that are parameters for this corrosive process to occur. The purpose of this work is to make a comparative study of a metal to be coated with nickel and Zn / Ni, this study will be analyzed through electrochemical tests, showing which coating is more resistant to corrosion, the corrosion tests for the samples were potential of corrosion as a function of time - EVT E and that of corrosimetry. According to the results, it was possible to conclude that the coating of 1020 steel with Nickel Metal is the most corrosion resistant sample when compared to the sample of the same metal used with Zn / Ni coated substrate.
Monografia
Keywords: Corrosão; Galvanoplastia; Testes eletroquímicos; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA